Herpes simplex virus‐induced anti‐N‐methyl‐d‐aspartate receptor encephalitis: a systematic literature review with analysis of 43 cases. (25th April 2017) - Nosadini, Margherita; Mohammad, Shekeeb S; Corazza, Francesco; Ruga, Ezia Maria; Kothur, Kavitha; Perilongo, Giorgio; Frigo, Anna Chiara; Toldo, Irene; Dale, Russell C; Sartori, Stefano
Abstract : Aim: To conduct a systematic literature review on patients with biphasic disease with herpes simplex virus (HSV) encephalitis followed by anti‐ N ‐methyl‐D‐aspartate receptor (NMDAR) encephalitis. Method: We conducted a case report and systematic literature review (up to 10 December 2016), focused on differences between herpes simplex encephalitis (HSE) and anti‐NMDAR encephalitis phases, age‐related characteristics of HSV‐induced anti‐NMDAR encephalitis, and therapy. For statistical analyses, McNemar's test, Fisher's test, and Wilcoxon rank sum test were used (two‐tailed significance level set at 5%). Results: Forty‐three patients with biphasic disease were identified (31 children). Latency between HSE and anti‐NMDAR encephalitis was significantly shorter in children than adults (median 24 vs 40.5d; p =0.006). Compared with HSE, anti‐NMDAR encephalitis was characterized by significantly higher frequency of movement disorder (2.5% vs 75% respectively; p <0.001), and significantly lower rate of seizures (70% vs 30% respectively; p =0.001). Compared with adults, during anti‐NMDAR encephalitis children had significantly more movement disorders (86.7% children vs 40% adults; p =0.006), fewer psychiatric symptoms (41.9% children vs 90.0% adults; p =0.025), and a slightly higher median modified Rankin Scale score (5 in children vs 4 in adults; p =0.015). During anti‐NMDAR encephalitis, 84.6 per cent of patients received aciclovir (for ≤7d in 22.7%; long‐term antivirals in 18.0% only), and 92.7 per cent immune therapy, but none had recurrence of HSE clinically or using cerebrospinal fluid HSV polymerase chain reaction (median follow‐up 7mo). Interpretation: Our review suggests that movement disorder may help differentiate clinically an episode of HSV‐induced anti‐NMDAR encephalitis from HSE relapse. Compared with adults, children have shorter latency between HSE and anti‐NMDAR encephalitis and, during anti‐NMDAR encephalitis, more movement disorder, fewer psychiatric symptoms, and slightly more severe disease. According to our results, immune therapy given for HSV‐induced anti‐NMDAR encephalitis does not predispose patients to HSE recurrence. What this paper adds: Movement disorder is characteristic of anti‐ N ‐methyl‐d ‐aspartate receptor (NMDAR) encephalitis but not of herpes simplex virus (HSV) encephalitis. Despite immune therapy for HSV‐induced anti‐NMDAR encephalitis, none of the patients had recurrence of HSV encephalitis. This review is commented on by Ellul and Griffiths on pages776–777 of this issue.